RCS Computation by Parallel MoM Using Higher-Order Basis Functions - Ying Yan; Yu Zhang; Chang-Hong Liang; Hui Zhao; D. García-Doñoro (International Journal of Antennas and Propagation)
A Message-Passing Interface (MPI) parallel implementation of an integral equation solver that uses the Method of Moments (MoM) with higher-order basis functions has been proposed to compute the Radar Cross-Section (RCS) of various targets. The block-partitioned scheme for the large dense MoM matrix is designed to achieve excellent load balance and high parallel efficiency. Some numerical results demonstrate that higher-order basis in this parallelized scheme is more efficient than the conventional RWG method and able to efficiently analyze RCS of various electrically large platforms.